Revisión de las tecnologías de conservación de agua para consumo y riego y su potencial aplicación en la cuenca alta del río Pastaza. - Silva Caiza, Lorena Yajaira (2022)
The population density growth into several world parts, as a urbanization and industrialization result has had a disastrous impact, about surface and groundwater. The water demand is consequently increasing and at the same time the "usable water resources" amount is for obvious reasons decreasing, due to human intervention into pollution form. It is for such motive, what the existing water resources protection, against pollution is an utmost importance aspect. For this reason, this research had to research water conservation technologies for consumption and irrigation, as well as, its potential application into Pastaza River upper basin. As a first step its elaboration, it was characterized the physical, social, and environmental study area aspects, by means reviewing information about the Pastaza hydrographic basin into sources, such as MAG, SENAGUA and INEC, INAMHI, MAE. Second, it was analyzed information about the different water conservation technologies from the oldest to actuality between the years 2005 to 2021; through the scientific articles collection and analysis, theses, books and documents related to the study subject, getting and analyzing a total 41 too 305 documents, what were included/excluded from study based on related criteria to language, application field, publication date and validity of the information; subsequently, the documentation was managed, through the Zotero bibliographic manager. As a third step, it was essential to select a related technologies series to water conservation with potential applicability into Pastaza River upper basin, those easy access and low cost, which it was proposed a proposal based on natural resource conservation strategies according its use. Among the got results, they could identify a 25 conservation technologies total for irrigation water and 18 for drinking water. It is suggested the application for irrigation water technologies such as infiltration trenches, water catchment, localized irrigation, software and programmers, while for drinking water technologies such as a water inventory with Arc map 10.1, River G device, fuzzy logic. Further, it was proposed a proactive and participatory management for the Pastaza River upper basin based about the water inventory creation, natural space recovery and protection, sources and flows care and protection, pollution control, water equitable distribution, waste control and permanent education. Finally, the actual research represents a great contribution to the water resources sustainable management, by mitigating the effects at benefiting all community members.